ADVANCING AN INTEGRATED MODEL OF RESILIENCE: CROSS-DISCIPLINARY AND CROSS-DOMAIN PERSPECTIVES. (11th November 2018) - Hawkley, L; Infurna, F J
Abstract: Resilience is generally understood as the process of adapting to adversity, and highlights human capacities and strengths even into oldest age. Domains of inquiry differ in how resilience is conceived and measured, and it is the goal of this symposium to explore some of this diversity and understand how resilience can be better conceptualized, assessed, and studied within and across domains. Hawkley considers functional resilience and describes the role of social relationships in helping ADL-dependent older adults minimize risk for depression, diminish their odds of ADL deterioration, and increase survival. Kim explores optimism as a modifiable intra-individual resilience resource and shows that optimism at baseline is associated with remaining free of major chronic disease, cognitive impairment, and physical disability over a 6-year follow-up. In her strength-based approach to aging, Nelson-Becker focuses on spiritual resilience as a resource to create purpose and meaning in the face of age-related losses. Whitson presents a conceptual framework for physical resilience that incorporates physiological, psychological, environmental, and social attributes, and discusses two methodological approaches to quantifying physical resilience using data from older adults hospitalized for an upper respiratory infection. As discussant, Infurna will seek to integrate these various perspectives on resilience, identify commonalities, and discuss implications for future research within and across domains of inquiry.